In vitro mass propagation protocol for an ornamental banana: explant sterilization to plantlet acclimatization - Siregar, Ahmad Syahrian; Mariani, Totik Sri; Rachmawati, Fitri; Rianawati, Sri; Winarto, Budi (Ornamental Horticulture, 2025)
The study investigates the critical factors in establishing an ornamental banana’s in vitro mass propagation protocol (Musa spp. ‘Pink Nono’) based on four important experiments. In the first experiment, testing three sterilization methods by applying varied-disinfectant agents revealed that high optimal clean shoots up to 92% with low contamination and 86% potential growth were proved by using a combination of streptomycin sulfate, and benomyl, 70% alcohol, 2.5% sodium, 0.1% HgCl2 hypochlorite, and reducing sucker size. In the second experiment, immersing the shoot tips in 0.1, 0.2, and 0.3 mg L-1 thidiazuron (TDZ) for an hour and culturing them in MS medium supplemented with 1, 2, and 3 mg L-1 N6-benzyl amino purine (BAP) proved that immersing shoots in 0.1 mg L-1 TDZ and then culturing them on MS medium containing 3 mg L-1 BAP resulted in high axillary shoots per explant up to 30.6 shoots. In the third experiment, 0.0, 0.5, and 1.0 g L-1 activated charcoal (AC) and mg L-1 α-naphthalene acetic acid (NAA) for root formation were tested, and it found that MS medium supplemented with 0.5 g L-1 AC and 1.0 mg L-1 NAA was optimal for root formation with 9.4 roots per shoot. Finally, three acclimatization media were researched, and it established that the high plantlet survivability of up to 93% was recorded in a combination of burned-rice husk, soil, organic manure, and volcanic sand (1:1:1:1, v/v/v/v) for treated plantlets previously. These insights provide a valuable protocol for producing high-quality planting materials efficiently.